Development of an Ultrasonication-Assisted Extraction Based HPLC With a Fluorescence Method for Sensitive Determination of Aflatoxins in Highly Acidic Hibiscus sabdariffa - Liu, Xiaofei; Ying, Guangyao; Sun, Chaonan; Yang, Meihua; Zhang, Lei; Zhang, Shanshan; Xing, Xiaoyan; Li, Qian; Kong, Weijun (Frontiers in Pharmacology, 2018)
The high acidity and complex components of Hibiscus sabdariffa have provided major challenges for sensitive determination of four trace aflatoxins. In this study, sample pretreatment of H. sabdariffa was systematically developed for sensitive high performance liquid chromatography-fluorescence detection (HPLC-FLD) after ultrasonication-assisted extraction, immunoaffinity column (IAC) clean-up and on-line post-column photochemical derivatization (PCD). Aflatoxins B1, B2, G1, G2 were extracted from samples by using methanol/water (70:30, v/v) with the addition of NaCl. The solutions were diluted 1:8 with 0.1 M phosphate buffer (pH8.0) to negate the issues of high acidity and matrix interferences. The established method was validated with satisfactory linearity (R >0.999), sensitivity (limits of detection and quantitation of 0.15-0.65 μg/kg and 0.53-2.18 μg/kg, respectively), precision (RSD <11%), stability (RSD of 0.2-3.6%), and accuracy (recovery rates of 86.0-102.3%), which all met the stipulated analytical requirements. Analysis of 28 H. sabdariffa samples indicated that one sample incubated with Aspergillus flavus was positive with aflatoxin B1 (AFB1) at 3.11 µg/kg. The strategy developed in this study also has the potential to reliably extract and sensitively detect more mycotoxins in other complex acidic matrices, such as traditional Chinese medicines, foodstuffs, etc.